Phytochemical analysis of mite‐infested tea leaves of Darjeeling Hills, India. Issue 3 (20th November 2019) - Banerjee, Piu; Islam, Md Moinul; Laha, Arghya; Biswas, Himani; Saha, Nimai Chandra; Saha, Goutam Kumar; Sarkar, Debjani; Bhattacharya, Srijit; Podder, Sanjoy
Abstract: Introduction: Darjeeling tea of India is one of the most famous beverages globally. However, a large amount of tea crop is damaged every year by the attack of mites. Objectives: The study aimed to determine the changes in different pigments and biochemical components of tea leaves due to mite infestation. Materials and Methods: We used UV‐visible and Fourier‐transform infrared (FTIR) spectroscopy simultaneously to understand the damages in pigment contents of the leaves of tea ( Camellia sinensis (L.) Kuntze) due to attack of phytophagus mite, Oligonychus coffeae Nietner. Furthermore, chemical analysis of infested tea leaves was also performed to compare the nutrients of the plants, namely total phenol, protein and soluble sugar. Results: The UV‐visible study reveals severe reduction of the pigments such as chlorophyll (Chl), carotenoids and xanthophylls in the tea leaf due to mite infestation. The findings of the FTIR study, also shows variation in different physiochemical components in the leaf Chl. The sugar and protein content of the infested leaves have been reduced compared to uninfested ones. Results in the case of tea leaves plucked during first (March) and third (November) flushes show similar trends. Conclusion: The increase in phenolic and alcoholic components and decrease in Chl contents may affect the quality of Darjeeling tea. The extent of damages done by the pests measured here could aid the pest management in tea gardens. Abstract : Darjeeling tea of India is damaged every year by the attack of a phytophagus mite, Oligonychus coffeae Nietner. UV‐visible and FTIR studies revealed that pigments like chlorophyll, carotenoids and xanthophylls have been reduced and the phenolic and alcoholic groups, pectin significantly increased due to mite infestation. The sugar and protein content of the infested leaves have also been reduced compared to uninfested ones. This study may enlighten the application of pest management in tea gardens.